The Art of Looking and Nature Writing: The Representation of Landscape and Nature in Esther Kinsky’s River - Pastuszka, Anna (Porównania, 2022)
In the novel River published in 2014, while wandering along the River Lea on the outskirts of London, the narrator observes an inconspicuous area that does not correspond to the traditional notion of the beauty of nature. The contemplation of the landscape finds its artistic expression not only in language that is not only extremely precise but also lyrical. The exploration of nature is also accomplished through the creative act of naming and describing the human and non-human world. Kinsky depicts a variety of landscapes: the area around the river with its mixture of nature and industry, urban and rural character, other riverine landscapes from the perspective of memories, and areas marked by war and violence. The subject’s attitude is characterized by resignation from an anthropocentric perspective that instrumentalizes nature. The aim of the article is to examine the mutual relations between the human being and the environment in the literary text, including the ecocritical perspective, as well as to investigate the aesthetic representation of landscape and nature in the novel.